PENERAPAN MODEL PROJECT BASED LEARNING PADA MATERI BARISAN DAN DERET ARITMATIKA DI SMK - Ismail Pamungkas; Zubaidah Zubaidah; Romal Ijuddin (Universitas Tanjungpura, 2019)
AbstractThis research aimed to know the effectiveness implementation of Project-Based Learning (PjBL) model in learning arithmetic sequence and series material at class X of SMK. The method used in this study was a pre-experimental method with One-shot case study. The aspects used to determine effectiveness by application the Project-Based Learning (PjBL) model was the implementation of learning by teachers in managing learning, student activities, and student learning outcomes. The data collection tool used is a test, student learning outcomes test which contains 6 essay questions, observation sheet of learning implementation of learning the teacher in managing learning, observation sheet of student activities, and research results data analyzed descriptively. It was found that the learning implementation process of learning by the teacher in managing learning was classified as good, namely (3.5). The activity of students is classified as active, which is equal to 64%. Classical learning completeness is not fulfilled, there are 25 students or 62.5%. Students who achieve the minimum completeness value, learning by application of Project-Based Learning (PjBL) model in arithmetic sequence and series material at class X of SMK Negeri 2 Pontianak are said to be ineffective. Keywords: Arithmetic Sequence And Series Material, Implementation of learning, Project-Based Learning (PjBL) Model.